Refiguring research stories of science identity by attending to the embodied, affective, and non-human - Rahm, Jrène; Gonsalves, Allison J. (Frontiers in Education, 2023)
This perspective article draws on conversations with a program coordinator in a community organization which guided the development of an after school Convoclub for girls, focused on understanding the role of science in their lives. We examine our conversations with the program coordinator to understand how affective placemaking, brought about by engagement in a digital storytelling project, created a new space for girls’ engagement in science. We describe these conversations as part of our “research story”—a term intended to highlight the importance of storying in postqualitative methods. We draw on data from a qualitative case study of the co-designed science activities in Convoclub with a special focus on conversations with its program director and our joint work in the design of the club activities over time(i.e., dialogue circles with the six youth participants, a digital storytelling project, and a video documentary about science). Presented in three vignettes, we address the evolution of the club activities and its implications for designing spaces for learning and becoming in informal science learning environments supportive of empowering identities in science understood through a framing in posthumanist perspective. Throughout, we consider the implications of refiguring research stories of identity by attending to the mundane yet also emergent stories of assemblages — affectively charged associations of people, places and thing. We consider what this orientation brings not only to the telling of identity stories, but to the co-design of learning spaces, and considerations about whose voices and whose stories are told and heard in science spaces.